The Energy Crisis in Germany and the Design of a Resilient Energy System - Tom Krebs (Forum for a New Economy, 2023)
This study analyzes the short-run effects on the German economy of the fossil energy crisis in 2022 and discusses some implications for the design of a resilient, renewable energy system. The study shows that the energy crisis led to a short-run output loss comparable to the output losses associated with the Covid-19 crisis in 2020 and the financial crisis in 2008. In addition, real wage losses during the energy crisis far exceed the corresponding losses during the Covid-19 crisis and the financial crisis. Finally, the economic costs of the energy crisis would have been much larger in a worst-case scenario that could be avoided through a combination of government decisions and luck. Thus, large negative shocks to the supply of energy have high economic costs, and the design of a future energy system that is resilient to such shocks should have the highest priority. The study discusses two requirements for a resilient energy system based on renewable energy and two policy instruments that can help meet these requirements. First, there is the need to deal with the risk that the production of renewable energy from wind and solar power is extraordinarily low for several weeks or months due to adverse weather conditions. For Germany, this requires the build-up of sufficient reserve capacity using (hydrogen-ready) gas-based power plants. Second, there is the need to provide sufficient capacity to generate electricity "in normal times" using variable renewable energy sources. Public insurance against long-run price risk for the producers of renewable energy can spur the necessary investment in wind and solar power. To ensure efficient use of public finances, these insurance contracts should be fair in the sense that from an ex-ante perspective the government neither gains nor loses money.
Keywords: E30; E32; E37; H12; Q40; Q43; Q48; 330; Energy crisis; cost of crisis; supply shocks; resilience; renewable energy; public insurance